2015
DOI: 10.3746/pnf.2015.20.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Effect of Resveratrol on the Structural Changes of Mice Liver and Kidney Induced by Cadmium; A Stereological Study

Abstract: Exposure to cadmium (Cd) has harmful effects on the liver and kidney. Resveratrol (RES) is an herbal substance that functions as a protective mediator. This study aimed to investigate the effects of RES on the histology of liver and kidney in Cd-exposed mice. Male mice were divided into 4 groups daily receiving normal saline (1 mL normal saline/d), Cd (1 mg/kg/d), RES (20 mg/kg/d), and Cd plus RES, respectively. After 4 weeks, the liver and kidney components were evaluated using stereological methods. The tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Therefore, the increased MMP-9 levels could be responsible for tissue collagen-reduced stain at the basement membrane level of both glomeruli and tubules demonstrated with SR stain. These morphological data seem to be in contrast with previous results from a stereological study on mouse kidney exposed for four weeks to CdCl 2 [ 19 ], where an increased volume of the fibrous tissue was observed in HE-stained specimens compared to controls. The differences could be related to the longer time of exposure to Cd in the work of Rafati et al [ 19 ], which could have induced a more serious hypoxia with increase in fibrosis [ 64 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, the increased MMP-9 levels could be responsible for tissue collagen-reduced stain at the basement membrane level of both glomeruli and tubules demonstrated with SR stain. These morphological data seem to be in contrast with previous results from a stereological study on mouse kidney exposed for four weeks to CdCl 2 [ 19 ], where an increased volume of the fibrous tissue was observed in HE-stained specimens compared to controls. The differences could be related to the longer time of exposure to Cd in the work of Rafati et al [ 19 ], which could have induced a more serious hypoxia with increase in fibrosis [ 64 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The proximal tubular epithelium, owing to its active role in reabsorption, is particularly sensitive to damage by oxidative stress, so that a possible link between Cd toxicity and renal cell injury was described [ 24 ]. However, Cd-induced structural changes of the glomeruli, consisting in increased mesangial matrix and glomerular swelling with wider urinary space, were also described [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Our study showed that Cd exposure resulted in hepatomegaly, which was consistent with previous studies. 29, 30 mMTs mRNA was induced by Cd both in livers and kidneys, which indicated that Cd had been transferred and released into the kidney which might result in renal damage. In line with these data, histological analysis showed glomerular shrinkage and tubular degeneration upon Cd exposure.…”
Section: Discussionmentioning
confidence: 96%